(untitled) (Historia, 2021)
English This article elucidates the key principles of satyagraha by noting how they evolved during the campaign of 1906 to 1914. It then seeks to analyse the extent to which the essence of satyagraha survived in struggles between 1915 and 1952. It argues for a recognition of earlier acts of satyagraha before the 1946-1948 passive resistance campaign. The article also examines the relevance of satyagraha in contemporary struggles over AIDS treatment and housing struggles. While the evidence suggests that there was a strong influence of satyagraha on several struggles in the 1930s to the 1950s, not all its principles were accepted and there was a whittling down and reshaping of its meaning. There were but a few adherents of satyagraha in its fullest meaning by the 1950s. Satyagraha has relevance for contemporary struggles largely because the wielder retains a strong moral high ground, but non-violent protest needs to be heeded by the democratic state. Gandhi’s abhorrence for a society based on unequal wealth and his concern for the poor have important contemporary relevance. Afrikaans Satyagraha in Suid-Afrika: Beginsels, Uitvoering en Moontlikhede Hierdie artikel verduidelik die sleutelbeginsels van satyagraha deur te kyk hoe dit gedurende die veldtog van 1906 tot 1914 ontwikkel het. Dit probeer vervolgens analiseer tot watter mate die wese van satyagraha in stryde tussen 1915 en 1952 oorleef het. Dit betoog ten gunste van die erkenning van vroeëre dade van satyagraha voor die passiewe weerstandsveldtog van 1946 1948. Die artikel ondersoek ook die betekenis van satyagraha in tydgenootlike stryde rondom die behandeling van Vigs en behuising. Terwyl die getuienis aandui dat satyagraha verskeie stryde van die 1930’s tot die 1950’s sterk beïnvloed het, is nie al die beginsels daarvan aanvaar nie, en is die betekenis daarvan gesnoei en hervorm. Teen die 1950’s was daar maar slegs enkele aanhangers van satyagraha in die volste betekenis daarvan. Satyagraha het betekenis vir eietydse stryde veral omdat diegene wat dit beoefen, ŉ sterk posisie op die morele hoë grond inneem, maar ook omdat vreedsame protes geneig is om die oor van die demokratiese staat te wen. Gandhi se weersin in ŉ gemeenskap gebaseer op ongelyke welvaart en sy besorgdheid oor armes het is ook van groot hedendaagse belang.